PROTEÇÃO DO CLIMA E CONSTITUIÇÃO – A DECISÃO HISTÓRICA DO TRIBUNAL CONSTITUCIONAL FEDERAL ALEMÃO DE 24 DE MARÇO DE 2021 - Kahl, Wolfgang (Revista da AJURIS, 2022)
CLIMATE PROTECTION AND THE CONSTITUTION – THE LANDMARK DECISION OF THE GERMAN FEDERAL CONSTITUTIONAL COURT ON MARCH 24, 2021 ÁREA(S): direito constitucional. RESUMO: A mudança climática mundial exige atualmente novas medidas no processo político, em especial no que concerne à implementação fática das normas e metas existentes para a proteção do clima na Europa e na Alemanha. A assim designada Climate Change Litigation se tornou uma tendência global, incluindo novos atores políticos e a atuação dos tribunais para instrumentalizar a proteção mais eficaz do clima, em face da capacidade limitada dos parlamentos em termos de sustentabilidade. Nesse contexto, o presente artigo aborda a decisão paradigmática do Tribunal Constitucional Alemão sobre a lei alemã de proteção do clima (KSG) e o seu impacto, em especial na esfera legislativa. ABSTRACT: Global climate change now requires new measures in the political process, in particular with regard to the practical implementation of existing climate protection norms and targets in Europe and Germany. The so-called Climate Change Litigation has become a global trend, including new political actors and the role of the courts to instrumentalize more effective climate protection in view of the limited capacity of parliaments in terms of sustainability. In this context, the present article addresses the paradigmatic decision of the German Constitutional Court on the German Climate Protection Act (KSG) and its impact, in particular on the legislative sphere. PALAVRAS-CHAVE: mudança climática; climate change litigation; Tribunal Constitucional Federal da Alemanha; direito ambiental. KEYWORDS: climate change; climate change litigation; Federal Constitutional Court of Germany; environmental law. SUMÁRIO: 1 Pano de fundo; 2 Climate Change Litigation como tendência global; 3 A questão em pauta; 4 Admissibilidade dos recursos de inconstitucionalidade; 5 O caráter fundamentado dos recursos de inconstitucionalidade; 6 Reação do legislador; 7 Por que uma decisão “histórica”?; 8 Perspectivas. SUMMARY: 1 Background; 2 Climate Change Litigation as a global trend; 3 The question at hand; 4 Admissibility of appeals of unconstitutionality; 5 The reasoned nature of the appeals of unconstitutionality; 6 Reaction of the legislator; 7 Why a “historic” decision?; 8 Perspectives.